2020
DOI: 10.1039/d0sc02685a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral information harvesting in helical poly(acetylene) derivatives using oligo(p-phenyleneethynylene)s as spacers

Abstract: A chiral harvesting transmission mechanism is described in poly(acetylene)s bearing oligo(p-phenyleneethynylene)s (OPEs) used as rigid achiral spacers and derivatized with chiral pendant groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Only a few examples related to chiral PDPAs [72–85] are found in the literature compared to the large amount of work that has been done with PPAs [12–33, 37–51, 94–97] . This is due to the difficulty of obtaining the former polymers in the laboratory by polymerization of the corresponding diphenylacetylene monomers (DPA).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few examples related to chiral PDPAs [72–85] are found in the literature compared to the large amount of work that has been done with PPAs [12–33, 37–51, 94–97] . This is due to the difficulty of obtaining the former polymers in the laboratory by polymerization of the corresponding diphenylacetylene monomers (DPA).…”
Section: Introductionmentioning
confidence: 99%
“… 51 65 Regarding the helical sense induction mechanism, some research groups have demonstrated the efficient long-distance transmission of chiral information for poly(isocyanide)s, 66 , 67 poly(vinylterphenylene)s, 68 , 69 and poly(acetylene)s. 70 73 Recently, our group has reported on poly[oligo( p -phenyleneethynylene)acetylene]s (POPEPAs), a novel family of helical polymers. 74 In these polymers, even though the chiral center is placed at a remote position from the backbone, a helix induction occurs due to the chiral arrangement of the achiral spacers, which is harvested by the polyene backbone. Hence, in a first step the stereogenic centers of the monomer repeating units (mru) command the achiral rigid oligo( p -phenyleneethynylene) (OPE) spacers to arrange with a specific tilting degree (Θ), the value of which depends on the absolute configuration of the chiral center.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamics revealed different communication mechanisms between components in both covalent and supramolecular copolymers. Therefore, different chiral amplification or chiral enhancement effects such as sergeants and soldiers, majority rules, chiral coalition, chiral accord, and chiral conflict have been observed. As a consequence, the common properties presented by these polymers have allowed the development of materials combining these two structural motifs. Regarding the helical sense induction mechanism, some research groups have demonstrated the efficient long-distance transmission of chiral information for poly­(isocyanide)­s, , poly­(vinylterphenylene)­s, , and poly­(acetylene)­s. Recently, our group has reported on poly­[oligo­( p -phenyleneethynylene)­acetylene]­s (POPEPAs), a novel family of helical polymers . In these polymers, even though the chiral center is placed at a remote position from the backbone, a helix induction occurs due to the chiral arrangement of the achiral spacers, which is harvested by the polyene backbone.…”
Section: Introductionmentioning
confidence: 99%
“…First theoretical studies were carried out for monomer (S)-1. The molecule was built up using the geometry determined from X-ray studies [68] as a starting point, and the most stable conformers were obtained using the CREST program. This revealed the presence of two major conformers at room temperature that contribute significantly to the spectra.…”
Section: Supplementary Materialsmentioning
confidence: 99%